Ecological and conservation status of Juniperus oxycedrus subsp. macrocarpa: A rare and endangered tree species in the flora of Libya - Saaed, Manam W. B.; Almasouri, Anwagy A. M. (Brawijaya University, 2025)
Preserving isolated plant populations and defining their geographic range, especially for rare and threatened species, is vital in conservation ecology. The current study examined the ecological status and potential conservation trajectories of Juniperus oxycedrus subsp. macrocarpa (Sm.) Neilr in the only Libyan area with significant populations of this tree. The habitat was identified, and its climatic, edaphic, and vegetation characteristics were analyzed. The species' landscape distribution was studied, with regeneration and mortality percentage estimated, along with influencing factors. The results revealed that the soil in the area is predominantly sandy in texture and infertile. The accompanying vegetation cover is comprised of 112 species and dominated by dwarf plant species. Previous records of this tree species east of Derna City are no longer extant. The study documented 4135 scattered trees covering an area estimated at around 260 hectares, with another 24 individuals located along the road to Al-Qubah city. The average height of the trees was 2.33 m, while the average canopy area and volume per individual were 38.18 m2 and 174.30 m3, respectively. The percentage of regeneration was estimated at 16.42%, while the mortality was 3.07%. Despite their apparent resilience to poor soil properties, arid climate, and proximity to the sea, this tree is primarily threatened by unsustainable human activities, resulting in habitat alteration and landscape modification. Therefore, urgent and efficient management measures are required to preserve this taxon at the national level. This should involve designating the study area as a protected zone to ensure long-term ecological conservation and sustainable management